An outsider on the Antarctic Peninsula: A new record of the non‐native moth Plodia interpunctella (Lepidoptera: Pyralidae) - Hugo A. Benitez; Carla Salinas; Jordan Hernández; Tamara Contador Mejías; Sanghee Kim; Claudia S. Maturana; Lorena Rebolledo; Laura M. Pérez; Paulo E. A. S. Câmara; Vinícius Alves Ferreira; Isabel Lobos; Alejandro Piñeiro; et al. (Ecology and Evolution, 2024)
Abstract We report the first record of the microlepidopteran Plodia interpunctella beyond the South Shetland Islands at the Chilean Yelcho scientific station (64°52′33.1428″ S; 63°35′1.9572″ W), Doumer Island, close to the west coast of the Antarctic Peninsula. It is notable that P. interpunctella, a globally distributed stored product pest species, exhibits a remarkable capacity for prolonged viability within food storage facilities. The dual challenges of food transportation and storage in the context of Antarctica's challenging operational conditions may have facilitated P. interpunctella's initial arrival to the Antarctic region. Non‐perishable food items, such as grains, flour and rice, provide practical options for the bulk food transportation and storage required in the long‐term operation of Antarctic research stations. The presence of P. interpunctella in Antarctica, even if restricted to synanthropic environments within buildings, is a clear threat to Antarctic biodiversity, not only through being an invasive species itself but also as a potential vector for other non‐native species (bacteria, acari, between others.), which could carry diseases to the native species.